Acute effects of haemodialysis on cutaneous microcirculation in patients with peripheral arterial occlusive disease. - Weiss, Thomas; Windthorst, Christiane; Weiss, Claus; Kreuzer, Jörg; Bommer, Jürgen; Kübler, Wolfgang (Nephrology, dialysis, transplantation, 1998)
BACKGROUND: Peripheral arterial occlusive disease (PAOD) is an increasing problem in patients on maintenance haemodialysis. Alterations in microvascular perfusion accompany and complicate arteriosclerosis of large vessels and might contribute to the disease process. The aim of the study was to investigate the acute effects of haemodialysis on the cutaneous microcirculation in 26 patients with and without intermittent claudication. METHODS: Cutaneous perfusion was assessed by measuring transcutaneous oxygen pressure (tcPO2) and skin temperature at the dorsum of the foot. After standardized cooling to 15 degrees C of a 2cm2 skin area, the time to reach baseline skin temperature was evaluated as an indirect parameter of reactive hyperaemia. RESULTS: During haemodialysis, tcPO2 dropped significantly in both groups. The decrease in tcPO2 was more pronounced in patients with PAOD (20% vs 15% n.s.). The reactive hyperaemia response was reduced significantly in patients with intermittent claudication indicated by a prolonged time to reach baseline skin temperature after cooling. Values of tcPO2 and reactive hyperaemia did not reach baseline values at the end of haemodialysis in either group. CONCLUSIONS: Nutritive skin perfusion is impaired during haemodialysis. These changes are more pronounced in patients with PAOD and persist after dialysis. These findings are relevant for the treatment of patients with vascular disease on maintenance haemodialysis.
Gesehen am 06.05.2024